Analitik Sampah: Eksplorasi Proyeksi Pengelolaan Sampah Kota Batam Menggunakan Pemrograman R - Gita Prajati; Suryo Widiantoro; Akhmad Rezki Purnajaya (Prosiding SISFOTEK, 2025)
The increasing amount of waste requires a better waste management plan. Batam is one of the cities in Indonesia with a high population and economic growth rate. Batam will need better waste management planning in the future. This study aims to project waste generation in Batam City. The study will be divided into three stages, namely secondary data collection, correlation analysis, and waste generation projection calculations. Secondary data collection will be carried out by collecting data from relevant agencies. Waste generation projections are made based on sociodemographic and socioeconomic factors using R programming. The results show that there are four variables with negative values, namely population, GDP, length of schooling, and literacy rate. Meanwhile, the variables of population density and economic growth rate have positive values. Waste generation projections were made using the variables of literacy rate, length of schooling, population size, and population density. As a result, waste generation in 2030 is projected to decrease to 0.592 kg/person/day.